Crystal structure of (4-(4-methoxyphenyl)-1H-pyrrole-3-carbonyl)ferrocene, C22H19FeNO2 - Zhou Yanhong; Zhang Chuan; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C22H19FeNO2, tetragonal, P42/n (no. 86), a = 21.7903(7) Å, c = 7.3022(4) Å, V = 3467.2(3) Å3, Z = 8, Rgt(F) = 0.0385, wRref(F2) = 0.1009, T = 170 K.